Dampak Penggusuran Kantin di Sekitar Kampus STKIP PGRI Sumatera Barat terhadap Kehidupan Sosial Ekonomi Pedagang Kantin - Jonri, Ali; Zusmelia, Zusmelia; Anggreta, Dian Kurnia (Pendidikan Sosiologi, 2013)
This study discusses about the cafeteria evictions around campus STKIP PGRI West Sumatera that give an impact on the socio-economic life of the former canteen vendors along Gunung Pangilun Street. The purpose of this study is to describe the impact of evictions around the campus cafeteria STKIP PGRI West Sumatera to the socio-economic life of the canteen and describe tradersâ strategies conducted in the cafeteria merchants to increase revenue after the eviction. The theory used in this study is the theory of social change by Neil Smelser. This study used qualitative methods with descriptive type. Data was collected through observation, interviews, and documentation. Informants in this study amounted to as much as 7 traders who trade around canteen STKIP PGRI Campus West Sumatra. Deliberate decision informant (purposive sampling) based on certain criteria. From the results of the study, it is found that the impact of evictions around the campus cafeteria STKIP PGRI West Sumatera to the socio-economic life of the canteen vendors. They are 1) The economic impact of a change in income or decrease in the amount of income trader canteen 20% to 30% and for some traders there which increased revenue by 85%. 2). Social impacts are: a). Tradersâ feel more comfort on early place than it was. b). The changing of Social relationships with merchants cafeteria customers. c). Social relationships among fellow traders established new cafeteria is stronger than before. d). There are also other changes such as a canteen lease rental is more expensive than the old cafeteria at the site, as well as electricity and water are available directly in the cafeteria. e). Constraints experienced after the eviction is influenced by the condition of the buyer in a particular day, the weather and the location of the canteen. Strategies used in the canteen merchants increase revenue after the eviction of providing facilities for costumers, provide good service for costumers, and providing food and drink menu diverse.